Exploring influential factors and strategies for addressing speech delay of a child with autism spectrum disorder (ASD) in English (L2) language acquisition - Mufidah, Nida (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Children with autism spectrum disorder (ASD) tend to exhibit a unique trajectory in the acquisition of language with some documented research. However, research investigating children with ASD in English (L2) language acquisition is limited, particularly in Indonesian ASD children. This research explores the factors that allowed this unanticipated foreign language acquisition, thereby causing delays in native speech, and investigates strategies that could help overcome the child's linguistic challenges. This case study research involved a six-year-old Indonesian ASD child experiencing early self-learning of English and speech delay in her native language. The data were garnered through observations, interviews, and field notes before being thematically analyzed. The results show that the internal factor of speech delay is prematurity, and the external influential factors are the high intensity of English language exposure through media, English daily interactions with family members, and the use of different first languages in the social environment. Successful strategies employed to acquire the child